Synthesis and physico-chemical properties of carbonyl derivatives of 4-((2,6-dichlorobenzylydene)amino)-5-(3-methylpyrazol-5-yl)-1,2,4-triazole-3-thiol - Fedotov, S. O.; Gotsulya, A. S.; Федотов, Сергій Олегович; Гоцуля, Андрій Сергійович (My University, 2024)
The aim of the work was the synthesis and investigation of the properties of 6-(2,6-dichlorophenyl)-3-(3-methylpyrazol-5-yl)-6,7-dihydro[1,2,4]triazolo[3,4-b][ 1,3,4]-thiadiazine-7-carboxylic acid and its carbonyl derivatives.
Keywords: тези доповідей